Dose‐dependent effect of impaired renal function on all‐cause mortality in patients following percutaneous coronary intervention. Issue 8 (27th June 2022) - Limpijankit, Thosaphol; Chandavimol, Mann; Srimahachota, Suphot; Kanoksilp, Anek; Jianmongkol, Poj; Siriyotha, Sukanya; Thakkinstian, Ammarin; Buddhari, Wacin; Sansanayudh, Nakarin
Abstract: Objective: To determine the risk prediction of various degrees of impaired renal function on all‐cause mortality in patients following percutaneous coronary intervention (PCI). Background: Patients with chronic kidney disease (CKD) are at high risk of all‐cause mortality after PCI. However, there are less data of various degrees of impaired renal function to predict those risks. Methods: This was a subgroup analysis of nationwide PCI registry of 22 045 patients. Patients were classified into six CKD stages according to preprocedure estimated glomerular filtration rate (eGFR) (ml/min/1.73 m 2 ): I (≥90), II (60−89), III (30−59), IV (15−29), or V (<15) without or with dialysis. Baseline clinical and angiographic characteristics were compared among patients in each stage. One‐year all‐cause mortality was reported with risk prediction based on CKD stages and other risk factors. Results: Patients with CKD stage I−V without and with on dialysis were found in 26.9%, 40.8%, 23.2%, 3.9%, 1.5%, and 3.7%, respectively. PCI procedural success and complication rates ranged from 94.0% to 96.2% and 2.8% to 6.1%, respectively. One‐year overall survival among CKD stages I−V was 96.3%, 93.1%, 84.4%, 65.2%, 68.0%, and 69.4%, respectively ( p  < .001 by log‐rank test). After adjusting covariables, the hazard ratios of all‐cause mortality for CKD stages II−V as compared to stage I by multivariate Cox regression analysis were 1.5, 2.6, 5.3, 5.9, and 7.0, respectively, ( p  < .001). Conclusion: Among patients undergoing PCI, lower preprocedure eGFR is associated in a dose‐dependent effect with decreased 1‐year survival. This finding may be useful for risk classification and to guide decision‐making.